Gambaran Penatalaksanaan Endorphin Masage Untuk Penurunan Skala Nyeri Punggung Bawah Ibu Hamil Trimester III di TPMB Bd. E Kecamatan Baregbeg - Pauziah, Widiya Sa’diyatil; Hindiarti, Yudita Ingga; Mukti, Arifah Septiane (Universitas Galuh, 2024)
Back pain during pregnancy typically occurs in the third Trimestr. This discomfort is especially common in the later stages of pregnancy, during the third trimester, when the body undergoes significant changes to accommodate the growing baby.in Indonesia reaches 60% -80%. Efforts to reduce pain can use Endorphin Massage to release endorphin compounds, which act as natural pain relievers. The aim of thist research is to determin the description of the management of endorpin masage to reduce the the scale of lowers bak pain in third trimestr pregnan women at TPMB Bd. E Baregbeg District. The method in this research uses descriptive. Sample wer taken fom a population that me the inclusin criteria, a sample of 13 people using an accidental sampling techniqu. The research instrumen used the Numeric Rating Scal (NRS) sheet and SOP. The results obtained before the Endorphin massage were carried out, most of the respondents experienced moderate pain, 7 respondents (53.8%) and after the Endorphin masage, almost all respondents experienced mild pain, with 10 respondents (76.9%). Base on the research results, it is evident that ther is a decreas in the scal of lower back pain in thir trimestr pregnan women after receiving Endorphin massage. It is hoped that midwives will apply and integrate Endorphin massage techniques to help reduce symptoms of back paint in thir trimestr pregnan women.